Research and Application of a Proppant Transport Experimental Device for Complex Fractures in the Unconventional Reservoir - Huan Peng; Yu Fan; Junliang Peng; Huifen Han; Xinping Gao; Liang Wang; Xinghao Gou; Yuelin Yin; Yuchao Zhou (Geofluids)
Due to the brittleness of the shale and tight reservoir and the development of natural fractures and horizontal beddings, complex fractures will be built by shear slip and tensile failure during multistaged horizontal well fracturing. Whether proppant can enter complex fractures and form effective support in main fractures and branch fractures determines conductivity of the complex fracture and stimulation effect of multistaged horizontal well fracturing. By means of discretization of disordered complex fractures, the orthogonal three-dimensional physical model of complex fractures is obtained and the complex fracture experimental device for simulating fracture complexity is developed and a complete set of proppant transport characteristic experimental device in unconventional reservoir complex fractures is formed. Combined with field parameters and lab experiments, the influence of proppant performance parameters and discharge capacity to proppant transport characteristics in complex fractures of the unconventional reservoir is studied. And on the basis of experimental results and analysis, the sensitivity analysis method is applied to analyze the influence degree of proppant transport characteristics in complex fractures of the shale or tight sandstone reservoir. The sensitivity order of influence factors is fracture morphology, proppant performance, liquid viscosity, displacement, and proppant concentration. The experimental device and research results can provide strong experimental support for the optimisation of shale or tight sandstone fracturing materials and field parameters.